The epidemiology of sickle cell disease in Germany following recent large‐scale immigration. Issue 7 (6th April 2017) - Kunz, Joachim B.; Cario, Holger; Grosse, Regine; Jarisch, Andrea; Lobitz, Stephan; Kulozik, Andreas E.
Abstract: Background: The epidemiology of sickle cell disease (SCD) in Germany is currently changing fundamentally with ongoing immigration. Here, we address the challenges resulting from the increased frequency, that is, the morbidity, and mortality of SCD in this population. Procedure: The number of immigrants with SCD was estimated based on the data of the German central registry of migrants (2007–2015) and published epidemiologic data. Additional data analysis was based on nationwide aggregated data from the diagnosis‐related groups' (DRG) statistics of the German Federal Statistical Office. Results: The total number of patients with SCD among migrants was estimated at 2, 016 in 2007 and 3, 216 in 2015, thus showing a 60% increase, which was particularly remarkable during 2014 and 2015. The countries of origin included those of West sub‐Saharan Africa, followed by Syria, and other countries of the Middle East. In parallel, the number of SCD inpatient treatments increased from 780 in 2002 to 1, 340 in 2015. Between 2012 and 2014, 42 patients with SCD died in hospital, mostly at an age of less than 5 years (n = 7) or over 30 years (n = 29). Conclusion: More than 3, 000 patients with SCD are estimated to live among the immigrant population in Germany. In addition, the number of SCD patients of German nationality is not known. The increasing number of inpatient treatments and the death of young children from SCD indicate the need for a general newborn screening program and an increased awareness of this disease among medical practitioners in a country in which SCD used to be rare.